Rheology of Pomelo Juice - Keshani, Samaneh (2009)
The proximate analysis studies on pomelo juice provide useful data for its juice processing industry. The studies on the physico-chemical properties such as water activity, pH and density make better prediction of its behavior at the relevant processing concentration and temperature. The Pomelo juice is found to have high moisture content which contributes to high water activity and specific heat of capacity. Also, the PH of pomelo juice obtained indicates that pomelo juice is acidic fluid. The predictions of density yielded high regression coefficient. In general, the density increases with increasing concentration but decreases with temperature increase. The density of pomelo juice also presented a stronger dependence on concentration than the temperature. Rheology is the science of deformation and flow behavior of fluid. Knowledge of rheological properties of fluid and their variation with temperature and concentration have been globally important for industrialization of food technology for quality, understanding the texture, process engineering application, correlation with sensory evaluation, designing of transport system , equipment design (heat exchanger and evaporator), deciding pump capacity and power requirement for mixing. The aim of this study was to determine the rheological behavior of pomelo juice at different concentrations (20-60.4 Brix) and temperatures (23-60°C) by using a rotational Haake Rheostress 600 rheometer and a cone and plate geometry sensor (35mm diameter, 2° cone angle), with a gap distance of 0.105 mm. Shear rates employed ranged from 0-1000 s-1. o Pomelo juice was found to exhibit both Newtonian and Non-Newtonian behavior. For lower concentration the Newtonian behavior is observed while at higher concentration Non-Newtonian behavior was observed. Standard error (SE) method was selected on the basis to carry out the error analysis due to the best fit model. For the four models the values of SE show that the Herschel-Bulkley and Power Law models perform better than the Bingham and Casson models but Herschel-Bulkley model is true at higher concentration. The experimental data of apparent viscosity versus shear rate were successfully described by the Power-law model. The model parameters; flow behavior index, n varied in the range of 0.65-0.89, whereas the values for the consistency coefficient, K, were in the range of 0.004-0.3 (Pa. ). Apparent viscosity and consistency coefficient of pomelo juice increased with increasing concentration and decreasing temperature. The effect of temperature on n was found to be significant but did not follow any descriptive trend. The effect of temperature on pomelo juice is best described by the applicability of the Arrhenius model related to apparent viscosity, η at a constant shear rate of 100s −1 or the consistency index of the power law model. Activation energies ( a Ε ) of the pomelo juice appeared in the range of 9103.83-23391.43 J/mol as the pomelo juice concentration was increased from 20 to 60.4 o Brix. The relationship between η or K of pomelo juice concentration was explained by exponential and power functions while pomelo juice observed that at higher concentration will have higher viscosity. The master-curve was investigated for comparing data from different products at a reference temperature of 40 . Multiple regression analysis indicated Master-Curve presents good agreement for pomelo juice at all concentrations studied with R 2 >0.8. oC Response surface methodology (RSM) was applied to investigate the effects of the three main independent parameters; rotation, temperature and time on the pomelo juice concentration and optimizing the operating conditions of the treatment process. Values of parameters required to obtain efficiency of concentration pomelo juice are suggested based on rotation speed (60-120 rpm), temperature (40-60 ) and time (5-60 min). oC It is clear from the result that the concentration increased when the temperature, rotation speed and time increased. It can be inferred that any parameters, individually, had positive effect on increase of concentration. The main effects of parameters are in following order: Main effect of time> temperature> rotation speed.